2015
DOI: 10.1063/1.4931962
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry reductions, exact solutions, and conservation laws of the generalized Zakharov equations

Abstract: In this paper, the generalized Zakharov equations, which describe interactions between high- and low-frequency waves in plasma physics are studied from the perspective of Lie symmetry analysis and conservation laws. Based on some subalgebras of symmetries, several reductions and numerous new exact solutions are obtained. All of these solutions represent modified traveling waves. The obtained solutions include expressions involving Airy functions, Bessel functions, Whittaker functions, and generalized hypergeom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…The results again shows that the conservation theorem presented by Ibragimov along with some of its extensions are shown to comprise a special case of a conservation identity (18) for the SA method.…”
Section: Comparison Of These Methods For Conservation Lawsmentioning
confidence: 62%
See 1 more Smart Citation
“…The results again shows that the conservation theorem presented by Ibragimov along with some of its extensions are shown to comprise a special case of a conservation identity (18) for the SA method.…”
Section: Comparison Of These Methods For Conservation Lawsmentioning
confidence: 62%
“…In general, for a given PDE system (1) expressed in a standard Cauchy-Kovalevskaya form, all non-trivial conservation laws arise from linear combinations of the PDE system (1) with multipliers that hold non-trivial divergence expressions [4,5,9,18]. In this paper, we suppose that (1) is expressed in a standard Cauchy-Kovalevskaya form.…”
Section: Direct Construction Methodsmentioning
confidence: 99%
“…In this part, we derive the optimal system of sub-algebras [4] of the vector fields in Equations (5)- (8). To do this, we begin by noting that each X i (i = 1, 2, 3, 4) yields an adjoint representation Ad(exp( X i ))X j , defined by [4] …”
Section: Optimal System Of Algebrasmentioning
confidence: 99%
“…In the last few decades, many scientists and mathematicians have extensively studied the dynamic behaviors of several PDEs using different concepts. Symmetry analyses have been used to study the PDEs [2][3][4][5][6]. It has been found that some new solutions to PDEs can be obtained from the old ones through symmetry transformations [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation